Multiplicação e conservação in vitro de Amburana cearensis (Allemão) A. C. Smith - Alvim, Bruno Freitas Matos (2012)
Amburana cearensis AC Smith, popularly known as "imburana–de-cheiro", "amburana-de-cheiro" and "cumaru", has wide distribution in regions of Caatinga and Cerrado. It stands out due to its multitude of uses, such as forage, food, timber and medicinal. By virtue of degradation of their natural habitats and predatory exploitation, it is listed as endangered species. The aim this study was to optimize the micropropagation protocol and develop a protocol for in vitro conservation Amburana cearensis. In the first chapter, for in vitro multiplication, were used different plant regulators (BAP, ANA, AIA, KIN) and explants (zygotic embryo, nodal and cotyledonary segments; in stage of rooting were tested auxins AIA, AIB, ANA and AIB combination with activated carbon . In the second chapter, was evaluated the effect of osmotic agents sucrose, sorbitol and mannitol and growth retardants paclobutrazol and ancymidol on vitro conservation of A. cearensis. The medium used in the experiments was the WPM supplemented with 87.64 mM sucrose, except in treatments using osmotic agent that contained variations in the concentration of sucrose. The best result was achieved for multiplication using nodal segments in culture environment added with1μM BAP and 0.05 μM ANA. The addition of 2 mM activated carbon associated with4μM AIB gave the best rooting percentages of shoots (54%). Supplementation of 262.92mM sucrose in the environment enabled the preservation of plants A. cearensis for 300 days with 77.5% survival.